Analisis Undang-Undang Nomor 42 Tahun 1999 Tentang Jaminan Fidusia dan Relevansinya Terhadap Fatwa DSN-MUI Nomor 68 Tahun 2008 Tentang Rahn Tasjily dalam pembiayaan Lembaga keuangan Syariah - Romli, Muhammad; Komarudin, Omay (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Debts are one of the activities that cannot be separated from society, because why, because debts are one form of way to fulfill every human need, whether for consumptive or productive interests. In this paper the author discusses Fiduciary Guarantee as a form of debt and its Relevance to the DSN-MUI Fatwa Number 68 of 2008 Concerning Rahn Tasjily in financing Islamic financial institutions. This paper uses a qualitative descriptive approach. The main data was collected from library data. The results of the study indicate that the fatwa of the National Sharia Council Number 68 of 2008 Concerning Rahn Tasjily, regarding guarantees in debts cannot be equated with Law Number 42 of 1999 Concerning Fiduciary Guarantees, because although basically the debts that are the object of the guarantee are goods, the goods can be registered as fiduciary or just collateral, which means pawn, so in essence the fatwa only discusses pawn guarantees, not fiduciary guarantees.